Health-Related Quality of Life, Physical Activity and Joint Health in People With Severe Haemophilia A Receiving Emicizumab : Results From the Phase IV HemiNorth 2 Study - Astermark, Jan; Ranta, Susanna; Myrin-Westesson, Linda; Hoffmann, Marianne; Quere, Sandrine; Sanchez, Amparo Yovanna Castro; Robson, Susan; Czirok, Tünde; Lassila, Riitta; Holme, Pål André (Haemophilia, 2025)
Introduction: Despite factor (F)VIII prophylaxis, a perceived increased risk of bleeding for some people with severe haemophilia A (PwSHA) exists, limiting physical activity (PA) and restricting quality of life (QoL). Aim: HemiNorth 2 (EudraCT# 2020-003256-32) is an interventional study evaluating the impact of switching from FVIII prophylaxis to emicizumab in PwSHA without FVIII inhibitors who have a need for improved prophylaxis in the Nordic countries. Methods: Following completion of the HemiNorth non-interventional study (NIS), eligible participants (aged ≥ 12–61 years) were enrolled in HemiNorth 2. The primary endpoint was health-related QoL via the Comprehensive Assessment Tool for Challenges in Hemophilia (CATCH). Secondary endpoints included PA (International Physical Activity Questionnaire-Short Form [IPAQ-SF]), treatment preference (Emicizumab Preference [EmiPref] survey), joint health, model-based annualised bleeding rates (ABRs) and adverse events. Results: Overall, 28 physically active male PwSHA were enrolled. Most baseline CATCH domains were ≤ 25 and remained consistent; mean treatment burden considerably improved from baseline for adults (−17.8) and adolescents (+16.7). IPAQ-SF scores were consistent throughout the study. Overall, 23 of 25 (92.0%) EmiPref respondents preferred emicizumab over FVIII prophylaxis. Model-based ABRs for treated bleeds decreased from 5.9 (95% confidence interval [CI]: 3.8–9.1) to 1.6 (95% CI: 0.9–3.0) from the NIS to HemiNorth 2, and participants with zero treated bleeds increased from 8 (28.6%) to 16 (57.1%). No new safety signals were reported. Conclusions: Emicizumab improved treatment burden and was preferred by most participants over FVIII prophylaxis. PA levels were consistently high, and bleeding rates improved with emicizumab versus prior FVIII prophylaxis.
Keywords: emicizumab; exercise; factor VIII; haemophilia A; physical activity